The meat crisis : developing more sustainable production and consumption - D'Silva, Joyce; Webster, John, 1938- (Earthscan, 2010)
"Meat and dairy production and consumption are in crisis. Globally sixty billion farm animals are used for food production every year. It is well accepted that methane emissions from cattle and other livestock are major contributors to greenhouse gas levels and to climate change. The Food and Agriculture Organization of the United Nations (FAO) predicts a rough doubling of meat and milk consumption by 2050, with particularly rapid growth occurring in the developing economies of Asia. This could raise the number of farm animals used annually to nearer 120 billion. What will this mean for the health and wellbeing of those animals, of the people who consume ever larger quantities of animal products, and for the health of the planet itself? This powerful and challenging book explores these issues surrounding the global growth in the production and consumption of meat and dairy animals and products, including cultural and health factors, and the implications of the likely intensification of farming for both small-scale producers and for the animals. Several chapters explore the related environmental issues, from resource use of water, cereals and soya, to the impact of livestock production on global warming and issues concerning biodiversity, land use and the impacts of different farming systems on the environment. A final group of chapters addresses ethical and policy implications for the future of food and livestock production and consumption. The overall message is clearly that we must eat less meat to help secure a more sustainable and equitable world"--Provided by publisher.